Minimally Invasive Triple Therapy of the Presurgical Neck - DeJoseph, Louis; Hojjat, Houmehr; Daraei, Paul Pedram (Facial Plastic Surgery, 2021)
Minimally invasive in-office procedures are a fast growing field in plastic surgery. Patients often notice and complain about their neck at an earlier age. Modern treatments for the aging neck have continued to evolve over the past decade, with more options continuing to become available. In this article, we describe our noninvasive approach to the aging neck through the combination of submental liposuction, radiofrequency (RF) microneedling, and percutaneous RF as a safe and effective option. Through appropriate patient selection, preoperative counseling, and good surgical technique, appropriate results can be achieved with minimal downtime. Patient selection, counseling, appropriate anesthesia, procedure details, and results are discussed in this article.
Keywords: neck rejuvenation; in-office procedure; minimally invasive; radiofrequency; neck; submental liposuction